Policy Area as a Potential Moderator of Transparency Effects: An Experiment. (6th April 2014) - de Fine Licht, Jenny
<x xml:space="preserve">Abstract</x> Building on the counterintuitive findings of recent empirical studies that transparency in political decision making may have a negative effect on public legitimacy beliefs, this article suggests that transparency has different effects depending on the policy area. Specifically, it argues that transparency is less effective in policy decisions that involve trade‐offs related to questions of human life and death or well‐being. Using an experiment that involved 1, 032 participants, the effect of transparency is tested in two policy areas that represent routine priority setting (culture and leisure) and policy decisions implicitly related to human life and well‐being (traffic security). Results indicate that transparency can increase public acceptance of political decisions, but this effect is moderated by the type of policy area. Furthermore, a limited type of transparency in which decision makers provide justifications for their decisions can result in benefits while avoiding potential costs.